Function of MicroRNAs in Normal and Abnormal Ovarian Activities: A Review Focus on MicroRNA-21 - Reza Arefnezhad; Hossein Roghani-Shahraki; Hossein Motedayyen; Fatemeh Rezaei Tazangi (International Journal of Fertility and Sterility, 2024)
Abstract:Some failures in ovary function, like folliculogenesis and oogenesis, can give rise to various infertility-associated problems, including polycystic ovary syndrome (PCOS) and premature ovarian insufficiency (POI). PCOS influences 8 to 20% of women; while POI occurs in at least 1% of all women. Regrettably, the current therapies for these diseaseshave not sufficiently been effective, and finding a suitable strategy is still a puzzle. One of the helpful strategies for managing and treating these disorders is understanding the contributing pathogenesis and mechanisms. Recently, it has been declared that abnormal expression of microRNAs (miRNAs), as a subset of non-coding RNAs, is involved in thepathogenesis of reproductive diseases. Among the miRNAs, the roles of miRNA-21 in the pathogenesis of PCOS and POI have been highlighted in some documents; hence, the purpose of this mini-review was to summarize the evidence in conjunction with the functions of this miRNA and other effective microRNAs in the normal or abnormal functions of the ovary (i.e., PCOS and POI) with a mechanistic insight.